Insurance and Sharia Cooperatives in Indonesia: (Philosophical, Historical, Juridical and Sociological Studies) - Wahyu Akbar; Mujiburohman, Mujiburohman; Ardiansyah, Mawar (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2023)
This paper aims to optimize Islamic insurance and cooperatives in Indonesia, which is reviewed from philosophical, historical, juridical and sociological studies. The method used is library research which examines literature which is analyzed qualitatively using a sociological approach, historical approach, juridical approach and philosophical approach. The results of the study show that insurance and cooperatives both carry the spirit of togetherness and help each other. The spirit of insurance and cooperatives is deeply rooted in Indonesian society, it's just that they are not institutionalized on a regular basis. The Indonesian government is trying to legally accommodate insurance and cooperatives in various laws and regulations, but there is still a need for firmness and clarity regarding the law on sharia insurance and sharia cooperatives, especially if there is a dispute. In addition, insurance and cooperatives need to improve their practice and understanding so that their benefits are felt by the community.